A Systematic Review of Educational Interventions based on Health Behavior Models for Promoting Pap Smear Testing in Iran - Bahmani, Afshin; Nili, Sairan; Sepehrian, Elahe; Khaledian , Fatemeh (Advances in Nursing & Midwifery, 2024)
Introduction: Cervical cancer is one of the most common cancers among women, and early detection through a Pap smear test plays an important role in timely diagnosis. This study aims to evaluate the type and degree of success of educational interventions based on health education theories and models in improving women’s participation in the Pap smear test in Iran. Methods: This research comprises a systematic review of studies published between 2010 and 2022 to synthesize existing knowledge on the effectiveness of educational interventions in increasing participation and performance of Pap smear tests. The search was conducted on databases such as Magiran, Science Direct, PubMed, Scopus, and SID, including all interventional studies (experimental and quasi-experimental). The search keywords included terms such as pap smear, screening, cervical cancer, educational models, theories of health education and educational interventions, which were reviewed in both Farsi and English languages. Results: Among the 3,171 articles initially extracted, 27 relevant interventional studies were included in this review. The intervention methods examined in these studies mostly include lectures, group discussions, questions and answers, educational videos, and multimedia messages in which more than one educational method is used. Times allocated to implement the interventions were different in each study. Approximately 62% of these studies were based on the health belief model, while others explored alternative health behavior models. The measured variables included various components of health education models, and most of these variables demonstrated significant improvement after the implementation of educational interventions among participants in the test group. Conclusions: This systematic review underscores the beneficial influence of targeted educational interventions in bolstering women’s engagement in Papsmear testing and cervical cancer prevention in Iran. The outcomes underscore the potential of health behavior models to guide future evidence-based educational programs aimed at promoting preventive healthcare practices among women.